THE INACCESSIBILITY OF JUSTICE FOR MIGRANT WORKERS: A CAPABILITIES-BASED PERSPECTIVE - Hastie, Bethany (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice, 2017)
This article examines the barriers migrant workers face in accessing justice, including the ability to assert legal rights in the workplace, and to access mechanisms for legal redress or remedy. Drawing on empirical research, and using the capabilities approach as a conceptual framework through which to examine these issues, this article demonstrates that the regulatory structure of the Temporary Foreign Worker Programs operates to actively constrain the ability for migrant workers to assert their rights in the workplace, and seek effective legal remedies in the face of rights violations.